Biomass resources and biofuels potential for the production of transportation fuels in Nigeria. (September 2016) - Ben-Iwo, Juliet; Manovic, Vasilije; Longhurst, Philip
Abstract: Solid biomass and waste are major sources of energy. They account for about 80% of total primary energy consumed in Nigeria. This paper assesses the biomass resources (agricultural, forest, urban, and other wastes) available in Nigeria and the potential for biofuel production from first, second, third and fourth generation biomass feedstocks. It reviews the scope of biomass conversion technologies tested within the country and the reports on the technology readiness level of each. Currently, most of the emerging biofuels projects in Nigeria utilize first generation biomass feedstock for biofuel production and are typically located many miles away from the petroleum refineries infrastructures. These feedstocks are predominantly food crops and thus in competition with food production. With significant availability of non-food biomass resources, particularly in the Niger Delta region of Nigeria, and the petroleum refineries located in the same area, it is pertinent to consider expanding use of the petroleum refinery׳s infrastructure to co-process non-food biomass into bio-intermediate oil for blending with petroleum. This not only addresses the potential food versus fuel conflict challenging biofuel production in Nigeria, but also reduces the cost of setting up new bio-refineries thus eliminating the transportation of ethanol to existing petroleum refineries for blending. In view of this, it is recommended that further research be carried out to assess the feasibility of upgrading existing refineries in Nigeria to co-process bio-based fuels and petroleum products thus achieving the targets set by the Nigeria Energy Commission for biofuel production in the country.